Effects of testing surface on performance time in a sled drag shuttle event - Hewit, J.; Jaffe, D.; Bigelman, K. (Journal of Trainology, 2019)
Objective: To compare performance times of a sled drag shuttle event over natural grass, synthetic turf, and sand surfaces in order to determine if one surface consistently produces faster performance times than the others. Design & Methods: Using a block randomized design, 25 active duty U.S. Army Soldiers performed one trial of the 250m sled drag shuttle event on each of the three testing surfaces; natural grass, synthetic turf, and sand. Total Event Time, Sled Drag Time and event time minus sled time (Event-Sled Time) were compared across the three surfaces. ANOVA with blocking and post hoc analysis were used to determine if there were significant differences in performance times between the three conditions. The alpha level was set at p = 0.05. Results: Both Sled Drag Time and Total Event Time were statistically faster when performed on synthetic turf (0.31 ± 0.05 min and 1.40 ± 0.11 min, respectively; p < 0.001). There was no statistical difference in performance time when sled time was eliminated from the total event time (p = 0.15). Conclusions: Testing surface does impact performance time in a sled drag shuttle event as performed in this study. If using such an event to assess and track physical performance or proficiency, it is recommended that subsequent testing take place on the same testing surface that was used for the baseline assessment. This will eliminate any performance advantages resulting from the varied testing environment.